Seasonal variation of avian diversity in Jamunkhadi Wetland Area, Jhapa, Nepal - Thapa Magar, Kalyani; Kunwar, Nischal; Limbu, Shivaraj; Rai, Tujin; Rai, Shusil Chandra; Tuladhar, Rohan; Thapa, Vishubha (Nepalese Journal of Zoology, 2025)
Wetlands are among the most productive ecosystems on the earth, supporting a variety of species and providing numerous ecological services to balance the ecosystem. This study analysed how seasonality affects bird species richness and diversity at the Jamunkhadi Wetland in Kankai Municipality, Jhapa District, eastern Nepal. Using point count and MacKinnon list methods, monthly surveys were conducted in winter from December 2023 to February 2024 and summer from March to May 2024. The study recorded 1060 birds, from 67 species, 32 families, and 15 orders. The most common order was Passeriformes, consisting of 31 species. The Shannon-Wiener diversity index was higher during winter (H = 3.20) than in summer (H = 3.19), while species evenness was higher in summer than in winter (J = 0.83 in summer, J = 0.80 in winter), but neither difference was statistically significant. Out of recorded species, 52 were resident and 15 were migratory: eight visited during winter, four visited during summer while three were partial migrants. Wetland-dependent species comprised an important component of the assemblage, with 13 species closely associated with wetland habitats. The great bittern (Botaurus stellaris) was a nationally endangered species along with four nationally near-threatened species- collared falconet (Microhierax caerulescens), the great cormorant (Phalacrocorax carbo), the blossom-headed parakeet (Psittacula roseata), and the Alexandrine parakeet (Psittacula eupatria). The wetland is an ecologically important station where migrants stop over on the Central Asian Flyway. Therefore, effective management and conservation are essential to minimize human impacts and protect habitats for both resident and migratory species.